DESIGN OF WORK EQUIPMENT SYSTEM AND STEAM SYSTEM WITH HYDRAULIC SYSTEM - Heri Wibowo (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2004)
The weight vehicle was used to work the weight job of human such as digging loading and lifting. the materials It was completed bv system work such as attachment svstem and driving system. The both of system must he supported by the engine follow with hydraulicsystem. Design 0/ attachment svst m used cylinder hydraulicmovement for work 01 digging. loading or lifting. and so do cylinder hydraulic was used to turning all bodv of vehicles. The movement and power a/attachment system and driving system was designed to could work a/digging. loading and lifiing. The result calculation of attachment force, the /ifi hvdraulic cylinder is designed with 2cvlinders. each has 15 em cvlinder diameter and I em width 0/cylinder with uses stainless steel (0., = 5100 kg/em']. The dump cylinder is designed with I cvlinder. has /8 CI7I ofcylinder diameter and I em width of cvlinder with lise the same materials. Hydraulic svstem uses the hydraulic pump to central work of attachment system and driving system [hut drive from engine power.